2020
DOI: 10.1017/jfm.2020.921
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence structure of neutral and negatively buoyant jets

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…However, in a turbulent fountain, where the buoyancy opposes the momentum, there is the dampening of turbulence in the flow as observed in our previous study (Talluru et al. 2021). For instance, in the seven experimental cases presented in this study, is highest for ; however, the turbulence intensity is maximum for , where the dampening effect of buoyancy is relatively reduced compared with .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, in a turbulent fountain, where the buoyancy opposes the momentum, there is the dampening of turbulence in the flow as observed in our previous study (Talluru et al. 2021). For instance, in the seven experimental cases presented in this study, is highest for ; however, the turbulence intensity is maximum for , where the dampening effect of buoyancy is relatively reduced compared with .…”
Section: Discussionsupporting
confidence: 66%
“…(2020) and the results have been validated in Talluru et al. (2021) and Milton-McGurk et al. (2021).…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…In a study by the present authors, the initial NBJ stage of the flow was investigated experimentally using two-dimensional particle image velocimetry (PIV) and planar laser-induced fluorescence (PLIF) (Milton-McGurk et al 2021;Talluru et al 2021). It was found that, like neutral jets and plumes, the velocity and buoyancy profiles take Gaussian shapes over a wide range of axial locations (20 z/D 40).…”
Section: Introductionmentioning
confidence: 98%
“…13 More recently, PIV and planar laser induced fluorescence (PLIF) have been used to simultaneously measure the velocity and scalar concentration fields 22 and to give a first description of the turbulent structure. 23 However, additional experimental datasets and interpretations are needed to understand (i) the complex interaction between the upflow and the counterflow and (ii) the phenomena related to the momentum and mass exchanges.…”
Section: Introductionmentioning
confidence: 99%